Functional and Genetic Insights into the Role of the NR4A1 Gene in the Litter Size of the Shaanbei White Cashmere Goat - Ebadu Areb; Yutian Bi; Yangyang Bai; Qihui Zhu; Lingyuan Ma; Chuanying Pan; Xiaolei Chen; Xianyong Lan (Animals, 2025)
Nuclear receptor subfamily 4 group A member 1 (NR4A1) plays a crucial role in regulating various physiological processes. As gene mining for reproductive traits is essential, this study aimed to investigate the mRNA expression, genetic variation, and association of the NR4A1 gene with goat litter size. We examined the mRNA expression levels of the NR4A1 gene in eight different tissues of female Shaanbei White Cashmere (SBWC) goats (n = 6). Then, a novel 11-bp insertion/deletion (InDel) variant was genotyped in 1136 SBWC goats, 87 SNPs were identified through resequencing (n = 120), and selection signal analysis was undertaken. The NR4A1 gene was expressed in all examined tissues, including the ovary and the oviduct, suggesting its role in goat reproduction. Both the 11-bp InDel and 13 SNP variants showed significant association with litter size. Additionally, four potential transcription factor binding sites were predicted within the insertion allele, which may contribute to increased litter size. Selection signal analysis revealed strong pressure on the NR4A1 gene region in the Cashmere goat population. These findings suggest that NR4A1 is a promising candidate gene for improving litter size in goats and could be utilized as a genetic marker in breeding programs.